Chromium and lead contamination in commercial poultry feeds of Bangladesh - Jothi, JS; Yeasmin, N; Anka, IZ; Hashem, S (International Journal of Agricultural Research, Innovation and Technology, 2017)
Heavy metals contamination into food chain is considered as an emerging crisis throughout the world especially in developing countries like Bangladesh. The concentration of heavy metals including Cr and Pb in commercial poultry feed samples (protein meal feed, meat and bone meal and fish meal feed) were detected by using Air/ Acetylene Flame Atomic Absorption Spectrophotometer. The mean concentration of heavy metals were found in protein meal feed in a range where Cr 10.63 to 218.10 mg kg-1 and Pb 7.37 to 52.25 mg kg-1. In meat and bone meal feed samples, Cr was recorded from 9.15 to 40.59 mg kg-1 and Pb 5.0 to 61.42 mg kg-1. Cr was found 17.68 to 78.39 mg kg-1 and Pb 3.54to 16.44 mg kg-1 in fish meal feed samples. However, results showed that all feed samples contained chromium and lead where both metals were present at alarming levels in most of the samples. It is therefore suggested that regular detection of heavy metals especially Cr and Pb should be done to evaluate the health risks and to protect the end user from food that might harmful for their health. Int. J. Agril. Res. Innov. & Tech. 6 (2): 57-60, December, 2016